Pengaruh Pendidikan Kesehatan tentang Bayi dengan Asfiksia terhadap Tingkat Pengetahuan Ibu Pasca Persalinan: The Effect of Health Education about Asphyxia Babies to the Knowledge Level of Postpartum Care Mothers in the Cempaka Room at Doris Sylvanus Hospital in Palangka Raya - Evy Kasanova; Suryagustina Suryagustina; Wiwi Dahlia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Background: Asphyxia is a condition in which newborn babies do not breathe spontaneously and regularly after birth; out of 120 million babies born with Asphyxia, nearly 1 million of these babies die because of Asphyxia. This is caused by fetal hypoxia in the womb associated with factors that arise in pregnancy, labor, and after birth. The high number of cases of death of infants with Asphyxia can be caused by a lack of knowledge of mothers in preventing the causes of Asphyxia during pregnancy to childbirth and how to treat Asphyxia in infants. Research Objective: To determine the effect of health education about Asphyxia on mothers' knowledge level in the Cempaka Room at dr. Doris Sylvanus Hospital Palangka Raya. Methods: This study used a Pre-experimental method with a one-group pre-post test design approach, a purposive sampling technique, and a Wilcoxon statistical test with 30 respondents. Research Results: Based on the results of statistical tests, the effect of health education on knowledge shows significance (ρ value = 0,000 <α 0,05), which means Ha is accepted so that there is an influence of health education about Asphyxia on knowledge of postpartum mothers in the Cempaka room at Doris Sylvanus Hospital Palangka Raya. Conclusion: The study's results show the influence of health education about Asphyxia on the knowledge of postpartum mothers. Suggestions for research sites are expected to be able to improve and maximize health promotion programs related to Asphyxia in infants to the knowledge of postpartum mothers, provide the latest information, and be used as input for health care institutions to reduce the incidence of Asphyxia to infants.